2014
DOI: 10.1556/aalim.43.2014.suppl.23
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of antioxidant components in roots of different red beets (Beta vulgarisL.) cultivars

Abstract: The beetroot is typically on the table in winter in form of pickles or juice, but for its nutritional values it would deserve more common consumption. Its curative effect in great part is due to the several vitamins, minerals, and compounds with antioxidant activity. But the division of biological active compounds is very different in the parts of the root. Based on our results, we could compare the differences between the morphology and some inner contents (soluble solid content, colour, betacyanin, betaxanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Similar results of root weight were presented in several studies with beetroot. Within the Austrian experiment (Wruss et al, 2015), the average root weight of seven beetroot cultivars ranged from 214 to 366 g. Székely et al (2014) found root weight variability of beetroot, depending on its cultivar, from 298.5 to 395.5 g in Hungary. The significant variability of root weight, depending on the beetroot cultivar, was presented by Nizioł-Łukaszewska and Gawęda (2014) in the study realised in Poland (83.7-336.7 g).…”
Section: Average Root Weightmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results of root weight were presented in several studies with beetroot. Within the Austrian experiment (Wruss et al, 2015), the average root weight of seven beetroot cultivars ranged from 214 to 366 g. Székely et al (2014) found root weight variability of beetroot, depending on its cultivar, from 298.5 to 395.5 g in Hungary. The significant variability of root weight, depending on the beetroot cultivar, was presented by Nizioł-Łukaszewska and Gawęda (2014) in the study realised in Poland (83.7-336.7 g).…”
Section: Average Root Weightmentioning
confidence: 97%
“…The beetroot (Beta vulgaris L. var. vulgaris) is a biennial vegetable species from the Amaranthaceae family (Székely et al, 2014). The beetroot (or red beet) is native to the Mediterranean area, and it is originated from the wild ancestor of Beta vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%
“…The results were provided in mg g -1 betacyanin DW and mg g -1 betaxantin DW dimension. The phenolic acids content was measured as described previously by Székely et al [14]. The separation of the phenolic components was done with Shimadzu HPLC instrument which consists of a gradients pump (LC 10), an UV-Vis detector (SDP-10A), a degasser (DGU-20A9), a column-thermostating unit (CTO-10A), a control unit (CBM-20A), and a computer software (LC Solution Software) that makes the processing and analysis of data easier.…”
Section: Methodsmentioning
confidence: 99%
“…Peroxidases (POX), polyphenol oxidases (PPO), ß -glucosidase, and betalain oxidase are the most responsible enzymes for betalain degradation during processing [ 14 , 37 ]. The disturbance of some endogenous enzymes can be overcome by blanching at 70 °C for 2 min [ 13 , 27 ]. Betalain colorants are available in the form of concentrates [ 44 ] and dried powder through air, freeze, or spray drying [ 43 , 45 ], and are normally used in dairy and confectioneries and even in meat products [ 27 , 46 ], although addition in cold products is preferable because of their thermal sensitiveness.…”
Section: Food Color Compoundsmentioning
confidence: 99%
“…Among the acknowledged sources of betalains, i.e., beetroot, swiss chard, dragon fruit, and prickly pear [3][4][5][6], beetroot has gained the most attention since, apart from the whole tuber, even their waste parts such as stalk [7], peel [8,9], and pomace [10,11] are rich in betalains. The ratio of color contents is decisively influenced by specie source, genetic, cultivar, or the environment of cultivation throughout growing, and the stages of harvesting [4,12,13]. Practically, one kilogram of fresh beetroot contains 300-600 mg of betacyanin and 320-420 mg of betaxanthin [14]; compared to the flesh, betalain concentration ranges from 40 to 70% higher in the peel and it also depends on genotypes [15].…”
Section: Introductionmentioning
confidence: 99%